The influence of resume quality and ethnicity cues on employment decisions - Shore, Ted; Tashchian, Armen; Forrester, William R. (Journal of Business Economics and Management, 2021)
This study examined the effects of resume writing quality and ethnicity cues on employment decisions. Prior research on resume quality is scant and no prior studies have examined the role of both resume quality and ethnicity on employment decisions. Participants reviewed a fictitious resume (error-laden or error-free) of a Black, Hispanic or White candidate for the job of Sales Manager. Applicants with error-laden resumes were less likely to be interviewed, hired, offered lower starting salaries and rated lower on job-related traits than applicants with error-free resumes. Although ethnicity did not affect the likelihood of getting interviewed or hired, White applicants were offered higher salaries and rated higher on several job-related traits than Black and Hispanic job applicants. Furthermore, Black applicants with error-free resumes received over 6% less in starting salary than White applicants with error-laden resumes. A practical implication of these findings is that applicants should ensure that their resume contains no spelling, grammatical or typographical errors. These results also suggest that non-White job applicants need job qualifications that exceed those of White applicants to achieve pay equity. This paper provides further evidence for and enhances understanding of implicit race bias toward non-White job applicants.First published online 29 October 2020